Evaluation of wireless home automation technologies - Rathnayaka, Dinusha; Potdar, Vidyasagar; Kuruppu, S. (IEEE, 2011)
Introduction of Wireless Home Automation (WHA) has become a positive inspiration to the new home and renovation projects, as it increases the quality of life and comfort of the inhabitants, simultaneously facilitating energy conservation and environmental sustainability. Generally WHA networks comprise of wireless embedded sensors and actuators that intelligently interconnect with each other through a suitable wireless architecture. Many wireless technologies have been emerged recently targeting WHA, hence selecting the optimal technology is challenging. In this article, we present an evaluation of these emerging wireless technologies and discuss their suitability for smart home networks.